1963
DOI: 10.1002/anie.196301562
|View full text |Cite
|
Sign up to set email alerts
|

Stable Free Radicals Formed by the Action of Sodium onto Diazomethane Derivatives or Phenyl Azide

Abstract: infrared and ultraviolet spectra and optical rotation) of the natural and synthetic products. Glycosidation of (2) was also effected when sodium iodide was used instead of silver perchlorate, or even without addition of either of these compounds, although then more vigorous reaction conditions were required. In this way we obtained a glucoside of uric acid from (2) and a-acetobromoglucose. This had the same ultraviolet spectrum (measured at pH 1, 7, and 14) as (1). This product, so far unknown in nature, is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…More recently an intermediate bonding situation has been discovered, in which the diazoalkane accepts only one electron. Although single electron reduction of diazofluorene with sodium metal was reported as early as the 1960s, 8 ligand radical character in transition metal or f-block metal diazoalkane complexes is rarely identified. 9 We have reported the cobalt diazoalkane complex L tBu Co(η 1 -N 2 CPh 2 ), 1-Co (L tBu = [{(Dipp)NC(tBu)} 2 CH] − where Dipp = 2,6-iPr 2 C 6 H 3 ), 10 which X-ray crystallographic and computational studies showed was best described as high-spin cobalt(II) antiferromagnetically coupled to the radical anion of diphenyldiazomethane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…More recently an intermediate bonding situation has been discovered, in which the diazoalkane accepts only one electron. Although single electron reduction of diazofluorene with sodium metal was reported as early as the 1960s, 8 ligand radical character in transition metal or f-block metal diazoalkane complexes is rarely identified. 9 We have reported the cobalt diazoalkane complex L tBu Co(η 1 -N 2 CPh 2 ), 1-Co (L tBu = [{(Dipp)NC(tBu)} 2 CH] − where Dipp = 2,6-iPr 2 C 6 H 3 ), 10 which X-ray crystallographic and computational studies showed was best described as high-spin cobalt(II) antiferromagnetically coupled to the radical anion of diphenyldiazomethane.…”
Section: ■ Introductionmentioning
confidence: 99%